MODEL DEVELOPMENT STRATEGY LEARNING 5MT (SQRACT) DIMENSIONS BASED PROCESS FOR ENHANCING COGNITIVE ABILITY TO READ THE SCIENTIFIC DISCOURSE UNDERSTANDING CLASS X SENIOR HIGH SCHOOL - Rina Andriani; Yeti Mulyati (Kopertis Region IV Jabar and Banten, 2019)
This study aims to develop and test the effectiveness of the strategy learning model 5MT (mengamati, menanya, membaca, menalar, mengomunikasikan, tes) (SQRACT= survey, question, read, association, communicating, test)) based on the dimension of the cognitive processes to improve reading comprehension of scientific discourse. The study was conducted using the method Reseacrh & Development, includes three phases: the planning, the development, and implementation stages.The implementation results showed among a control group with the experimental group, there is a significant difference of 0.005 <0.05. While learning to read when they see the results of scientific discourse understanding gained significant difference of 0.009 <0.05 between who have high scientific attitude and students who have low scientific attitude, and if the relationship between reading comprehension of scientific discourse with a scientific attitude is not there a significant relationship 0.985>0.05. Thus the authors can improve reading comprehension while enhancing the ability to think of High Order Thinking class X SMAN Ciparay Bandung regency in the academic year 2015/2016